Adjunct Use of Low-Level Laser Therapy on the Treatment of Necrotizing Ulcerative Gingivitis: A Case Report - SEVİNÇ ÖZBERK, SEDA; GÜNDOĞAR, HASAN; ŞENYURT, SÜLEYMAN ZİYA; ERCİYAS, KAMİLE (Journal of Lasers in Medical Sciences, 2017)
Necrotizing ulcerative gingivitis (NUG) is a microbial disease of the gingiva in the context of an impaired host response. This form of gingivitis is relatively rare. NUG is an infection characterized by gingival necrosis presenting as “punched-out” papillae, spontaneous bleeding, pain, oral malodor, and pseudomembrane formation. The primary predisposing factors are bacterial plaque and an inadequate diet, but smoking and psychological stress may also affect the disease severity. NUG is associated with a characteristic bacterial flora, which includes fusiform bacteria, spirochetes, and Prevotella intermedia. Conventional treatment includes control of both the bacterial plaque and the secondary factors, as well as topical or systemic treatment biostimulative effect on wound healing, pain control, and inflammatory processes. Patients with NUG were treated using adjunct use of a diode laser (980 nm) for the control of pain and to accelerate the wound healing at day 2. 3. 5. 9, energy density was 9 J/cm2. After treatment, the patients’ quality of life improved faster than with conventional treatment. These results suggest that low-level laser therapy (LLLT) is an effective treatment for the reduction of pain levels and healing times. As a result, our case report shows that LLTT has a positive effect in relieving the symptoms of NUG.